Layer-by-layer assembled membranes from graphene oxide and polyethyleneimine for ethanol and isopropanol dehydration. (28th April 2020) - Halakoo, Elnaz; Feng, Xianshe
Graphical abstract: Highlights: Crosslinked (PEI/GO)z LbL membranes were designed and fabricated. More than threefold increase in separation factor for dehydration of EtOH and IPA. Membrane resistance for permeation of different alcohol/water mixtures was calculated. The membrane performance can be fine-tuned by controlling number of bilayers. Abstract: Novel thin film composite membranes based on layer-by-layer (LbL) self-assembly of polyethyleneimine (PEI) and graphene oxide (GO) on chlorine-treated polyamide membranes were prepared for pervaporation dehydration of alcohols. To improve the membrane perfoarmance, the self-assembled bilayers were crosslinked with glutaraldehyde. A two-level factorial design was used to determine the effects of the main factors involved in the membrane preparation and their interactions on the permeation flux and separation factor. The impacts of the number of bilayers on the membrane performance were considered to gain an insight into the mass transfer resistance contributed by the bilayers. At 60 °C, the crosslinked (PEI/GO)7 LbL membrane showed a flux of 1770 and 1494 g/m 2 h for ethanol/water and isopropanol/water mixtures, respectively, at 2 wt% water in feed, with a corresponding separation factor of 77 and 197. The long-term stability test showed the feasibility of the crosslinked membranes for alcohol dehydration.